2013
DOI: 10.1542/peds.2012-0627
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Parental Incarceration on the Physical and Mental Health of Young Adults

Abstract: This study suggests exposure to parental incarceration in childhood is associated with health problems in young adulthood. Extant literature suggests underlying mechanisms that link parental incarceration history to poor outcomes in offspring may include the lack of safe, stable, nurturing relationships and exposure to violence. To prevent poor health in offspring of the incarcerated, additional studies are needed to (1) confirm the aforementioned associations and (2) assess whether adverse experiences and vio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
205
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(214 citation statements)
references
References 44 publications
5
205
2
2
Order By: Relevance
“…4 Research, including meta-analytic studies, link poor mental and physical health across the lifecourse with unstable family contexts such as interpersonal family violence, 5,6 parental suicide, and incarceration of a family member. [7][8][9][10][11] Although the negative impact of these exposures is established, only 1 study to date has examined the association between any of these exposures and telomere length, an established biological indicator of cellular aging and, more recently, toxic stress. 12,13 Exposure to early adversity increases risk for negative health outcomes across the life course, [14][15][16] yet it is unclear whether specific experience or cumulative exposure is the most biologically toxic.…”
Section: Resultsmentioning
confidence: 99%
“…4 Research, including meta-analytic studies, link poor mental and physical health across the lifecourse with unstable family contexts such as interpersonal family violence, 5,6 parental suicide, and incarceration of a family member. [7][8][9][10][11] Although the negative impact of these exposures is established, only 1 study to date has examined the association between any of these exposures and telomere length, an established biological indicator of cellular aging and, more recently, toxic stress. 12,13 Exposure to early adversity increases risk for negative health outcomes across the life course, [14][15][16] yet it is unclear whether specific experience or cumulative exposure is the most biologically toxic.…”
Section: Resultsmentioning
confidence: 99%
“…This evidence suggested that parental incarceration may lead to a cycle of substance abuse and incarceration in their offspring [14][15][16][17]. Lee, Fang, and Lou [18] found a high risk of HIV/AIDs in an adult sample who had incarcerated parents.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Compared to children of parents who had no history of imprisonment, children who had a parent in prison had more mental health problems [4] and psychosocial stress [5] due to the separation from their parents, loneliness, stigmatization, labile childcare agreements and uncertain home and school environments. Lee et al [6] investigated the correlation between parental imprisonment and children's physical and psychological health based on data from a national longitudinal study. The results showed that there was a significant correlation between parental imprisonment and health difficulties, such as asthma, migraines, depression, posttraumatic stress disorder and anxiety.…”
Section: Introductionmentioning
confidence: 99%